RELATIONSHIP OF HARDINESS, OPTIMISM AND PROFESSIONAL LIFE STRESS AMONG HOUSE-JOB DOCTORS - Jamal, Yousaf (Journal of Postgraduate Medical Institute, 2017)
Objective: This study investigated the relationship of hardiness, optimism and professional life stress among house-job doctors serving in five public teaching hospitals in Lahore, Pakistan. Methodology: A cross-sectional survey research design was used in this research using a purposive sample of 200 (118 males and 82 females). Personal views survey third edition (PVS-III), life orientation test revised (LOT-R) and professional life stress scale (PSS) were used to measure the hardiness, optimism and stress respectively. The Statistical Package for the social sciences (SPSS) version 20.0 for window was used for analysis of data. Results: Male constituted 59% of the sample with age ranging from 22 to 32 years for both genders. Hardiness and optimism accounted for 29% variance on professional life stress. The relationship of hardiness and professional life stress was significant (p <0.001). Conclusion: Hardiness was found as significant predictor of professional life stress among house-job doctors. However there was absence of any relationship between optimism and professional life stress.